Researcher Profile: An Interview with Axton Betz-Hamilton - Axton Betz-Hamilton (Journal of Financial Therapy, 2015)
Dr. Axton Betz-Hamilton teaches consumer studies courses at Eastern Illinois University, including Personal and Family Finance, Housing, and Consumer Issues. She conducts research on identity theft as well as financial abuse within families.
Keywords: financial therapy; financial abuse; identity theft; consumer studies